Pelaksanaan Manajemen Pendidikan Inklusi di MAN 2 Sleman - Muhammad Hudaifah Nurcholis Al Fatah; Difa’ul Husna; Muhammad Hatta Minulyo; Raikhan Daizona (PT. ALHAFI BERKAH INDONESIA, 2023)
The purpose of this research is to understand how inclusive education management can be managed and run at MAN 2 Sleman. This research is classified as a type of qualitative research with a descriptive approach. In this study using purposive sampling method. The data collection methods used involved interviews, observation, and documentation. Participants in this study included the school board, children with special needs, teachers assisting children with special needs, and parents of children with special needs. Data analysis involved collecting, reducing, presenting and reviewing data. The findings of the study indicate that the management of inclusive education at MAN 2 Sleman is good. This is indicated by checking the data through the data evaluation section. The results of observations, interviews and documents show that MAN 2 Sleman's participatory education management consists of eight areas, namely curriculum, student affairs, funding, teachers and employees, community relations, culture and education.